2002
DOI: 10.1126/science.1066642
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin-Domain Proteins Required for Maintenance of Ventral Nerve Cord Organization

Abstract: During development, neurons extend axons along defined routes to specific target cells. We show that additional mechanisms ensure that axons maintain their correct positioning in defined axonal tracts. After termination of axonal outgrowth and target recognition, axons in the ventral nerve cord (VNC) of Caenorhabditis elegans require the presence of a specific VNC neuron, PVT, to maintain their correct positioning in the left and right fascicles of the VNC. PVT may exert its stabilizing function by the tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
146
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(154 citation statements)
references
References 12 publications
7
146
0
1
Order By: Relevance
“…Its precisely mapped and invariantly structured nervous system allows to probe with unprecedented detail the effect of removing individual cells and genes. Genetic and cellular ablation studies have revealed that a number of diverse Ig domain proteins are required to maintain the precise positioning of axons within fascicles and cell bodies within ganglia (Zallen et al 1999;Aurelio et al 2002;Bü low et al 2004;Sasakura et al 2005;Wang et al 2005;Bénard et al 2006;Pocock et al 2008). Intriguingly, without these molecules nervous system development is unaffected, yet precise neuroanatomical patterns are lost postdevelopmentally.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Its precisely mapped and invariantly structured nervous system allows to probe with unprecedented detail the effect of removing individual cells and genes. Genetic and cellular ablation studies have revealed that a number of diverse Ig domain proteins are required to maintain the precise positioning of axons within fascicles and cell bodies within ganglia (Zallen et al 1999;Aurelio et al 2002;Bü low et al 2004;Sasakura et al 2005;Wang et al 2005;Bénard et al 2006;Pocock et al 2008). Intriguingly, without these molecules nervous system development is unaffected, yet precise neuroanatomical patterns are lost postdevelopmentally.…”
mentioning
confidence: 99%
“…When such movement is inhibited, these displacing forces are absent and consequently maintenance factors are no longer required (Aurelio et al 2002;Sasakura et al 2005;Bénard et al 2006;Pocock et al 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The locations of neuronal soma, axons, and dendrites must be maintained to ensure proper nervous system function during the addition and removal of neurons and synapses and in response to mechanical stresses associated with body growth and movement. The factors maintaining nervous system architecture are often distinct from those involved in its establishment during development, a division of labor which likely allows flexibility to cope with the stresses involved in remodeling, growth, and movement.The involvement of extracellular matrix components, cell adhesion molecules, and cytoskeletal proteins in previously reported neural maintenance activities demonstrate that adhesive cell-matrix and possibly cell-cell interactions play a critical role (Aurelio et al 2002;Bulow et al 2004;Sasakura et al 2005;Wang et al 2005;Benard et al 2006Burket et al 2006;Pocock et al 2008;Woo et al 2008; Zhou et al 2008). Although previously unreported, factors controlling nuclear position in neurons may also be predicted to play key roles in positional maintenance of neuronal soma.…”
mentioning
confidence: 99%
“…The involvement of extracellular matrix components, cell adhesion molecules, and cytoskeletal proteins in previously reported neural maintenance activities demonstrate that adhesive cell-matrix and possibly cell-cell interactions play a critical role (Aurelio et al 2002;Bulow et al 2004;Sasakura et al 2005;Wang et al 2005;Benard et al 2006Burket et al 2006;Pocock et al 2008;Woo et al 2008; Zhou et al 2008). Although previously unreported, factors controlling nuclear position in neurons may also be predicted to play key roles in positional maintenance of neuronal soma.…”
mentioning
confidence: 99%